2014
DOI: 10.1002/cbin.10352
|View full text |Cite
|
Sign up to set email alerts
|

Lithium chloride suppresses LPS‐mediated matrix metalloproteinase‐9 expression in macrophages through phosphorylation of GSK‐3β

Abstract: Abnormal degradation of matrix components due to dysregulated expression of matrix metalloproteinase (MMP)-9 in macrophages has been linked to progression of acute cerebral ischemia and atherosclerosis. We report that lithium chloride (LiCl) or CHIR99021, inhibitors of Wnt signaling pathway, enhance phosphorylation of glycogen synthase kinase-3beta and suppress lipopolysaccharide-mediated upregulation of MMP-9 expression in murine macrophage RAW264.7 cells in a dose-dependent manner. Suppression of MMP-9 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Furthermore, pharmacological induction of β-Catenin by CHIR99021 was able to reactivate matured cardiomyocytes and therefore suggested as a future approach for regeneration after myocardial infarction (Fan et al, 2018). The same compound has been reported to suppress MMP9 release from macrophages in vitro (Kim et al, 2015) which also implies a potential use in BBB protection after cerebral I/R injury. Our current results might help in designing future in vivo assessment of this approach according to the biphasic regulation of the Wnt signaling cascade.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, pharmacological induction of β-Catenin by CHIR99021 was able to reactivate matured cardiomyocytes and therefore suggested as a future approach for regeneration after myocardial infarction (Fan et al, 2018). The same compound has been reported to suppress MMP9 release from macrophages in vitro (Kim et al, 2015) which also implies a potential use in BBB protection after cerebral I/R injury. Our current results might help in designing future in vivo assessment of this approach according to the biphasic regulation of the Wnt signaling cascade.…”
Section: Discussionmentioning
confidence: 97%
“…Even though many studies have indicated that LiCl can regulate some biological processes, such as inflammation, apoptosis, and glycogen synthesis, the mechanisms involved in these processes are not well understood 1820. Furthermore, it has been reported that LiCl enhances osteogenesis in wear particle-induced osteolysis via Glycogen synthase kinase-3β (GSK-3β) signaling pathway inhibition and attenuates osteoclastogenesis by suppressing the nuclear factor-kappa B (NF-κB) pathway 19,21. In addition to these biological processes, the effects of LiCl in regulating inflammation in different immune cell models, especially macrophages, in the context of inflammatory diseases, have also been explored 2224.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase (MMP)‐9 was associated with abnormal degradation of the extracellular matrix when its production by macrophages was deregulated. Lithium treatment was found to suppress MMP‐9 gene expression and reduce the level of this metalloproteinase , thereby reducing plaque instability. Vascular smooth muscle cell (VSMC) proliferation and migration in the intima of the arterial wall also play an important role in atheroma progression .…”
mentioning
confidence: 99%